Inferring pain experience in infants using quantitative whole-brain functional MRI signatures: a cross-sectional, observational study - Duff, E; Moultrie, F; van der Vaart, M; Goksan, S; Abos, A; Fitzgibbon, S; Baxter, L; Wager, TD; Slater, R (Elsevier, 2020)
Background In the absence of verbal communication, it is challenging to infer an individual's sensory and emotional experience. In communicative adults, functional MRI (fMRI) has been used to develop multivariate brain activity signatures, which reliably capture elements of human pain experience. We aimed to translate whole-brain fMRI signatures that encode pain perception in adults to the newborn infant brain, to advance understanding of functional brain development and pain perception in early life.